IMPACT OF COVID – 19 ON UROLOGICAL INTERVENTIONS AT TERTIARY REFERRAL HOSPITAL - Subihardi, Lalu Muhammad Editia; Renaldo, Johan; Soebadi, Mohammad Ayodhia (Indonesian Journal of Urology, 2023)
Objective: This study aims to identify and evaluate the impact of COVID-19 on urological interventions at Soetomo general-academic hospital as the tertiary referral center. Material & Methods: This study is a descriptive-retrospective, single-center study that included all confirmed cases of COVID-19 in urological patients from March 1, 2020 until December 31, 2021 at Soetomo general-academic hospital. We investigated these patients' characteristics, focusing on the demography, clinical data, and eventual outcome. Patient's gender, age, primary urological presentation, COVID-19-related symptom, comorbidity, chest x-ray result, and laboratory value were among the involved variables. The patient's outcome was categorized into death, delayed intervention, or intervention as scheduled. Results: Seventy-seven patients were enrolled, with a mean age of 44.2 years. Fever was found in 42 (54%) patients and respiratory symptoms in 32 (41.5%) patients. An NLR value of >6 was found in 55.8% of patients. A total of 18 patients experienced LUTS (23.4%), 33 patients presented with hematuria (42.9%), and 30 patients had urinary tract infections (39%). Nineteen out of 77 patients (27.3%) died before intervention. On the other hand, surgical intervention in 37 (66%) patients were delayed due to self-isolation, while intervention in 19 (34%) patients was performed as scheduled due to their emergency nature. Conclusion: Urological patients infected with COVID-19 were impacted by the delay of surgical procedures and mortality in the first 22 months of the pandemic.